Development of Security Identification and Monitoring System for Web Application - Dani, Norizawati (1999)
Security is an essential entity to any software application. The most famous threat to any software application is unauthorized updating and deleting of the application and data. Characteristics of a software application that could contribute to the degree of security concerns are accessibility, forgery, vulnerability and density. If the software application contains most of these characteristics, the more vulnerable it would be to any security threats. Thus, a web application being an open application and contains all of the characteristics faces the most degree of security concern and open to all possibility security threats such as hacker, eavesdropping and spooling. A security system that would secure the web application from most of the security threats is crucially needed. The findings of this research is in the form of a prototype of a security system specifically for a web application. The web application that it secures is a knowledge application. The prototype is called SecureApp. It is developed by using Microsoft Visual Basic as its development tool and Microsoft Access as its database package. SecureApp consists of two main applications which are User Identification and Security Administration. These applications follow a predetermined security policy developed to protect the web application. Theory of encryption is used in its design and development for both applications especially to secure the passwords. SecureApp gives solution to the problem of securing a web application from any unauthorized users and other threats. The Security Administration application would allow the Security Administrator to monitor and detect any users who tries to b reach the security policy of the web application. Whereas, the User Identification application would secure the web application and ensure that the security policy of the web application is not breached.